Intracellular Virus Dynamics A Study of The Converting from The Deterministic Model to its Stochastic Counterpart (Al-Mukhtar Journal of Basic Sciences, 2026)
By examining both deterministic and stochastic models, the intracellular viral movement model explores the complex dynamics of the interaction of viruses with host cells. Since such movement is not deterministic but rather random, the main goal of this study is to build a stochastic model corresponding to the deterministic one, that describes the movement of viruses and their intracellular interactions in a more realistic way. The model helps explain how viruses are produced and reproduce by analyzing the mechanisms that generate and deplete structural proteins and viral nucleic acids, and by examining the effect of the viral template, the findings may help improve methods for treating and preventing viral infections by shedding light on structural proteins and viral DNA. The deterministic and stochastic systems were solved numerically and represented using MATAB tools, to gain deeper insights.